THE USE OF REALISTIC MATHEMATICS EDUCATION IN TEACHING THE CONCEPT OF EQUALITY - Theodora, Febe Ratu Nada; Hidayat, Dylmoon (Universitas Pelita Harapan, 2018)
Algebra is one of the most fundamental concepts in learning mathematics and the concept of equality is an essential part of learning algebraic topics. However, many students find this concept difficult to understand. The problem is the difficulty of the content and how to teach it. In order to solve the problem, this paper reviews the use of the theory of Realistic Mathematics Education (RME) in teaching the concept of equality. RME is a process of teaching and learning mathematics in a contextual way as mathematics is considered as a human activity. This paper aims to review the use of the RME theory in teaching the concept of equality within the Biblical perspective as the parameter of the implementation for mathematics as one of God’s tools to reveal His glory and wisdom. The method used in this paper was literature review which used literature findings as the resources. According to the literature research, it was found that the main problem in teaching and learning the concept of equality was students’ misconception of equality. The use of the RME theory can help teachers to teach the “equality” concept to help student learn contextually. BAHASA INDONESIA ABSTRAK: Aljabar merupakan salah satu konsep paling dasar dalam pembelajaran matematika mendalam dan konsep persamaan merupakan bagian yang penting dalam mempelajari topik-topik aljabar. Namun ada murid-murid yang mendapati bahwa konsep persamaan sulit dimengerti. Permasalahannya adalah seputar sulitnya materi yang dipelajari dan cara pengajarannya. Untuk mencari solusi dari permasalahan tersebut, makalah ini akan mengkaji penggunaan teori Matematika Realistis dalam pengajaran konsep persamaan. Matematika Realistis adalah proses belajar mengajar matematika kontekstual yang memandang matematika sebagai aktifitas manusia. Makalah ini bertujuan untuk mengkaji penggunaan teori Matematika Realistis dalam pengajaran konsep persamaan di dalam perspektif Alkitabiah sebagaimana matematika adalah alat Allah untuk menyingkapkan kemuliaan dan hikmat-Nya. Metode yang digunakan dalam makalah ini adalah studi literatur yang menggunakan temuan-temuan literatur sebagai sumber. Berdasarkan studi literatur, masalah utama dalam pengajaran konsep persamaan adalah adanya miskonsepsi pada pemahaman murid dan menggunakan teori Matematika Realistis, pengajar dapat mengajar konsep “keseimbangan” untuk membantu murid belajar secara kontekstual.